Functional Non‐Nucleoside Adenylyl Cyclase Inhibitors. (6th November 2014) - Lelle, Marco; Hameed, Abdul; Ackermann, Lisa‐Maria; Kaloyanova, Stefka; Wagner, Manfred; Berisha, Filip; Nikolaev, Viacheslav O.; Peneva, Kalina
<x xml:space="preserve">Abstract</x> In this study, we describe the synthesis of novel functional non‐nucleoside adenylyl cyclase inhibitors, which can be easily modified with thiol containing biomolecules such as tumour targeting structures. The linkage between inhibitor and biomolecule contains cleavable bonds to enable efficient intracellular delivery in the reductive milieu of the cytosol as well as in the acidic environment within endosomes and lysosomes. The suitability of this synthetic approach was shown by the successful bioconjugation of a poor cell‐permeable inhibitor with a cell‐penetrating peptide. Additionally, we have demonstrated the excellent inhibitory effect of the compounds presented here in a live‐cell Förster resonance energy transfer‐based assay in human embryonic kidney cells.